SPE Annual Technical Conference and Exhibition 1999
DOI: 10.2118/56538-ms
|View full text |Cite
|
Sign up to set email alerts
|

Oilwell Cement Durability

Abstract: This paper was prepared for presentation at the 1999 SPE Annual Technical Conference and Exhibition held in Houston, Texas, 3–6 October 1999.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 4 publications
0
11
0
1
Order By: Relevance
“…Temperatures within this range of tobermorite stability have been recommended as optimum curing temperatures to prevent strength retrogression during early curing stage (Saunders and Walker, 1954 (Hara et al, 1978;Nelson et al, 1981;Henmi and Kusachi, 1992;Merlino et al, 2001;Matsushita et al, 2004;Richardson, 2008;Churakov, 2009). Above 150 o C, a moderately permeable but strong calcium silicate hydrate phase, called xonotlite (C 6 S 6 H), is formed (Noik and Rivereau, 1999;Fabienne et al 2002;Brand et al, 2011). Truscottite, which is formed at about 215 o C, is a weaker but less permeable form of tobermorite and may transform to xonotlite in its stable form.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperatures within this range of tobermorite stability have been recommended as optimum curing temperatures to prevent strength retrogression during early curing stage (Saunders and Walker, 1954 (Hara et al, 1978;Nelson et al, 1981;Henmi and Kusachi, 1992;Merlino et al, 2001;Matsushita et al, 2004;Richardson, 2008;Churakov, 2009). Above 150 o C, a moderately permeable but strong calcium silicate hydrate phase, called xonotlite (C 6 S 6 H), is formed (Noik and Rivereau, 1999;Fabienne et al 2002;Brand et al, 2011). Truscottite, which is formed at about 215 o C, is a weaker but less permeable form of tobermorite and may transform to xonotlite in its stable form.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…In addition to the C-S-H polymorphs above, other structural forms, including an amorphous gel phase, might be produced at different temperatures and C/S ratios. Their structure, mineralogy and relative weights are characterized using techniques such as Fourier Transform Infrared (FTIR), Scanning Electron Microscopy (SEM), X-Ray Diffraction (XRD) and Neutron Magnetic Resonance (NMR) (Noik and Rivereau, 1999;Fabienne et al 2002;Le Saout et al, 2004, 2006a, 2006bNeuville et al, 2012;Lesti et al, 2013).…”
Section: C-s-h (I) C-s-h (Ii)mentioning
confidence: 99%
“…It was concluded that alternative cements have to be used to guarantee long term integrity for H 2 S injection wells. Noik and Rivereau (1999) designed a "reactive powder cement (RPC)" composed of API class G with sand and silica fume. The system mixed at 15.8 lbs/gal (ppg) had a low water:cement ratio of 0.27 resulting in low water permeability of less than 10 -6 mD after curing at 356 °F for 3 months.…”
Section: D Cement Corrosion Due To Dissolving Attackmentioning
confidence: 99%
“…Asimismo, también existen estudios sobre el ataque químico a cementos petroleros en condiciones de altas temperaturas y presencia de ácido sulfhí-drico en el yacimiento (8); mientras muy pocos son los trabajos que han estudiado el efecto combinado de ambos gases agrios sobre los citados cementos a altos valores de presión y temperatura (9).…”
Section: Introductionunclassified
“…Moreover, there are also works on the chemical attack on petroleum cements at high temperatures and in the presence of hydrogen sulfide in the reservoir (8). However, there are very studies on the combined effect of both sour gases on these cements at high pressure and temperature (9).…”
Section: Introductionmentioning
confidence: 99%